2005
DOI: 10.1103/physrevb.71.184521
|View full text |Cite
|
Sign up to set email alerts
|

Spin currents in superconductors

Abstract: It is argued that experiments on rotating superconductors provide evidence for the existence of macroscopic spin currents in superconductors in the absence of applied external fields. Furthermore it is shown that the model of hole superconductivity predicts the existence of such currents in all superconductors. In addition it is pointed out that spin currents are required within a related macroscopic (London-like) electrodynamic description of superconductors recently proposed. The spin current arises through … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…This novel phenomenon offers the exciting possibility of pure electric driven spintronics in semiconductors, which can be more readily integrated with current industry. Recently, the observations of the spin Hall effect have been reported [8,9,10] in GaAs based devices, which has generated an intensive research [11,12,13,14,15,16]. However, up to now, most of the experimental measurements were concentrated on GaAs system.…”
mentioning
confidence: 99%
“…This novel phenomenon offers the exciting possibility of pure electric driven spintronics in semiconductors, which can be more readily integrated with current industry. Recently, the observations of the spin Hall effect have been reported [8,9,10] in GaAs based devices, which has generated an intensive research [11,12,13,14,15,16]. However, up to now, most of the experimental measurements were concentrated on GaAs system.…”
mentioning
confidence: 99%
“…This is consistent with absence of a charge current but it allows for the existence of a spin current, where electrons of opposite spin orbit in opposite directions. This is what happens in the superconducting state according to the theory of hole superconductivity [30,44,46]. Thus, within this theory there is no puzzle associated with inward radial motion of electrons in the rotating superconductor.…”
Section: E Radial Motion and Existence Of Spin Currentmentioning
confidence: 69%
“…This was the expectation of Becker et al [9], they stated: "Wir beschränken unsere Betrachtungen von vornherein auf die Rotationsbewegung der Elektronen, vernachlässigen also die dureh die Zentrifugalkraft bedingte negative Aufladung der Kugeloberflache", meaning "We restrict our considerations from the beginning to the rotational motion of the electrons, neglecting the negative charging of the surface caused by the centrifugal force". In references [28] and [29] it was also concluded that negative charges would move out because of an incorrect analysis of the radial forces involved [30], and the authors presumably did That physical intuition is in fact flawed for the case of a perfect conductor. A perfect conductor starting from rest would indeed develop a magnetic field as the electrons near the surface lag behind the motion of the ions, and the Lorentz force due to this magnetic field would pull the electrons slightly inward.…”
Section: The Radial Electric Fieldmentioning
confidence: 99%
“…The investigation of these effect is particularly interesting. The breaking of particle-hole symmetry, even at half filling, is a generic property of real materials and creates effects on the paramagnetic phase [15], besides the frustration of the antiferromagnetic phase [16]. The effect of nonrandom NNN hopping becomes evident already in the noninteracting system through an asymmetric density of states (DOS), as already derived for an arbitrary hopping on the Bethe lattice [17].…”
Section: Introductionmentioning
confidence: 73%